What are the Main Diagnoses in Hospitalized Patients in Madagascar ? A Sentinel Surveillance in 18 Hospitals from 2014 to 2018 - Laurence Randrianasolo; Tojonirina Rabehasimbola; Léa Randriamampionona; Mireille Randria; Toky Ramarokoto; Barivola Bernardson; Feno Manitra Rakotoarimanana; Maherisoa Ratsitorahina; Roland Razanatsimba Andriamasoandro; Hasina Alain Randimbitsialonina; Hajalalaina Razafindrazaka; Jery Soa Bakolitiana Rafaliarisoa; et al. (Journal of Epidemiology and Global Health)
Abstract Background In Madagascar, a sentinel surveillance system was set up in 18 hospitals since 2014 and was managed by the Ministry of Public Health and the Institut Pasteur de Madagascar. In order to improve the access to appropriate health care in Madagascar, the main clinical diagnoses in hospitalized patients were analyzed. Methods At hospitalization of a patient, each unit involved in the sentinel surveillance recorded the clinical diagnosis through an e-health platform. Data from September 2014 to July 2018 were analyzed. Morbidity and annual incidence of diseases according to ICD-10 were reported. Results A total of 140,789 inpatients information was recorded. The median age was 28.2 years (IQR: 18.3; 45.3). 21.6% of the children < 15 years suffered from communicable diseases. The hospital morbidity was 4.01% for malaria, 0.84% for tuberculosis, 0.09% for HIV/AIDS and 0.05% for plague. The hospital morbidity of non-communicable diseases was higher compared to communicable diseases with 7.8%, 7.1% and 3.1% for ”Diseases of the circulatory system”, "Injury, poisoning and certain other consequences of external causes" and "Mental and behavioural disorders”, respectively. "Pregnancy, childbirth and puerperium" represented 20.5% of the hospitalized patients. Conclusions The e-health platform enabled continuous and standardized data collection. Communicable diseases affect mainly children < 15 years. Non-communicable diseases are on the rise and need more attention by national health authorities. A number of hospitalizations could be prevented by a better health care management at the community-based health care level and by implementation of a Universal Health Coverage (UHC) in Madagascar.